Analysis of the Learning Culture of Grade 6 Students of Satit Phatnawitya Yalla Elementary School Thailand - Ruhiyat, M. Deni; Adri, Helmia Tasti; Laeli, Sobrul (ALACRITY : Journal of Education, 2024)
Learning culture is the process of creating habits in students, so that a sense of awareness arises in carrying out activities without having to be ordered because it is already ingrained in the student. The aim of this research is to find out and investigate the learning culture of grade 6 students at Satit Phatna Withya Elementary School, Yala, Thailand, including routine activities that have become habits and school culture. The results of the learning culture analysis show that the way students often learn becomes the way they learn. These habits become students' learning culture. A good culture that is responsive to students' circumstances will produce good learning. Studying a culture is a series of activities in which students routinely carry out learning tasks. The success of learning in the world of education is determined by students' study habits. In the class of students who are starting to use technological resources, the learning culture of grade 6 students at Satit Phatna Witya Elementary School, the teaching method that is often used in learning is a combination of discussion methods, lecture methods and practice methods.